Experimental investigations on behaviour of cold formed steel stub uprights - Mohan, Vimal; Jayachandran, Arul; Kallapa, M.S. (Journal of Structural Engineering, 2024)
Uprights act as a column member in the rack system. In pallet racking systems, all upright sections are perforated to accept the hooks of the beam end connector and are the heart of the structural system. The perforations not only play an important role in the rack industry (for holding component in place), but are prone to more problems compared to any other form of structural member without perforation. The present study focuses on the behavior of perforated uprights under axial concentric loading. For better understanding, experiments were conducted on four specimens of steel rack uprights, by varying the thickness of sections as 1.6 and 1.8 mm with limitation on the slenderness ratio 10 and 18. Experimental investigations on the cold formed upright sections were studied for different type of configuration and their results are presented. Stress distribution across the specimen is also presented.